2017
DOI: 10.20886/jphh.2017.35.3.197-209
|View full text |Cite
|
Sign up to set email alerts
|

SIFAT FISIS DAN MEKANIS PAPAN UNTAI BERARAH DARI BAMBU TALI (Gigantochloa apus (J.A. & J.H. Schultes) Kurz)

Abstract: Bamboo is potential as an alternative material to substitute wood. This paper examines the effects of using different resin contents and strand dimensions on the properties of its oriented strand board (bamboo OSB). Tali bamboo (Gigantochloa apus (J.A. & J.H. Schultes) Kurz) was used as raw material in manufacturing the bamboo OSB. Laboratory scale oriented bamboo strand boards were fabricated using each bamboo strand length (7.5, 10, and 15 cm) and glued with liquid phenol formaldehyde adhesive at various res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
1
0
0
1
Order By: Relevance
“…The values of MOR parallel to the surface grain of bamboo-based OSB in this study were higher than those of OSB, as reported in previous studies (Suzuki and Takeda 2000;Sumardi et al 2008;Hidayat et al 2013;Febrianto et al 2015;Sulastiningsih et al 2017;Iswanto et al 2019;Lunguleasa et al 2021;Zhuang et al 2022a). All MOR values of bamboo-based OSB in this study met the JIS A 5908 (2015) requirements for type 24-10 (OSB type) particleboard (24 and 10 MPa).…”
Section: The Morsupporting
confidence: 81%
“…The values of MOR parallel to the surface grain of bamboo-based OSB in this study were higher than those of OSB, as reported in previous studies (Suzuki and Takeda 2000;Sumardi et al 2008;Hidayat et al 2013;Febrianto et al 2015;Sulastiningsih et al 2017;Iswanto et al 2019;Lunguleasa et al 2021;Zhuang et al 2022a). All MOR values of bamboo-based OSB in this study met the JIS A 5908 (2015) requirements for type 24-10 (OSB type) particleboard (24 and 10 MPa).…”
Section: The Morsupporting
confidence: 81%
“…Penelitian Suhadi et al, (2018) Lembaran OSB yang telah dibentuk, pada bagian atas lembaran dilapisi kembali dengan aluminium foil dan diberi lapisan plat seng. Pengempaan dilakukan pada suhu 160℃, dengan waktu kempa bervariasi 8 menit, 10 menit dan 12 menit, dan tekanan kempa sebesar 35kg/cm 3 ( Sulastiningsih et al, 2017). Papan OSB yang telah jadi selanjutnya dilakukan pengkondisian pada suhu kamar selama ± 7 hari sebelum dilakukan pengujian.…”
Section: Industriunclassified
“…Pengolahan bambu menjadi produk bambu lamina hanya memanfaatkan bambu berdiameter besar, berdinding tebal dan berbatang lurus. Dalam proses pembuatan bilah bambu dihasilkan limbah berupa bilah dengan ukuran yang tidak teratur sehingga tidak bisa digunakan untuk pembuatan bambu lamina (Sulastiningsih, Indrawan, Balfas, Santoso, & Iskandar, 2017). Di samping itu, dari proses penyerutan bilah bambu dihasilkan limbah berupa partikel bambu dengan volume yang cukup besar.…”
Section: Pendahuluanunclassified